Coating composition and electrochemical device and electronic device comprising same
By using a combination of modified melamine salt and binder in an electrochemical device, the physical and chemical characteristics are regulated, and the safety of the electrochemical device under high temperature and mechanical impact is solved, and the storage performance and safety are achieved. performance.
Patent Information
- Application Number
- CN202411804176.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2044-12-10
AI Technical Summary
Electrochemical devices are prone to explosion under conditions such as high temperature and mechanical impact, and existing inactive material coatings cannot effectively improve their high temperature storage performance and mechanical safety performance.
Using a composition of modified melamine salt and binder, the endothermic temperature, solubility, thermal weight loss mass residual rate, particle size and mass percentage content of the modified melamine salt are combined with different molecular modifiers and binders. The type of the electrochemical device forms a suitable coating composition to improve the high temperature storage performance and mechanical safety performance of the electrochemical device.
It significantly improves the storage performance and mechanical safety performance of electrochemical devices at high temperatures, reduces the risk of overheating and explosions, while maintaining normal operating performance.
Smart Images

Figure CN119286317A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of electrochemical technology, and in particular to a coating composition and an electrochemical device and an electronic device comprising the same. Background Art
[0002] Electrochemical devices (such as lithium-ion batteries) have the advantages of high energy storage density, high open circuit voltage, low self-discharge rate, long cycle life, and good safety. They are widely used in various fields such as energy storage, mobile electronic devices, electric vehicles, and aerospace. As mobile electronic devices and electric vehicles enter a stage of rapid development, the market has put forward higher and higher requirements on the energy density and safety performance of electrochemical devices. However, electrochemical devices are usually prone to explosion when subjected to heat exposure, penetration, collision, impact, etc., and their safety performance needs to be improved.
[0003] The existing technology usually adopts a coating layer including alumina, boehmite, barium sulfate, magnesium oxide and other inactive materials on the surface of the diaphragm to reduce the possibility of overheating and explosion of the electrochemical device. However, when the above-mentioned inactive materials are used in the coating layer, the transmission of lithium ions and electrons in the diaphragm and the positive electrode sheet has no interaction, resulting in poor stability of the electrochemical device, which in turn affects the high-temperature storage performance and mechanical safety performance of the electrochemical device. At this stage, the market demand for electrochemical devices with good high-temperature storage performance and mechanical safety performance is increasing. Summary of the invention
[0004] The purpose of the present application is to provide a coating composition and an electrochemical device and an electronic device comprising the same, so as to improve the high temperature storage performance and mechanical safety performance of the electrochemical device.
[0005] It should be noted that in the invention content of this application, lithium-ion batteries are used as an example of electrochemical devices to explain this application, but the electrochemical devices of this application are not limited to lithium-ion batteries. The specific technical solutions are as follows:
[0006] The first aspect of the present application provides a coating composition, the coating composition comprising a modified melamine salt and a binder, wherein the endothermic temperature characterized by the modified melamine salt on the differential scanning calorimetry (DSC) curve is lower than the endothermic temperature of the unmodified melamine salt, and the difference is Δt, 5°C≤Δt≤100°C. Compared with the unmodified melamine salt, the modified melamine salt has a lower endothermic temperature and can regulate the thermal decomposition temperature. By using the modified melamine salt in the coating composition and regulating Δt within the scope of the present application, the high temperature storage performance and mechanical safety performance of the electrochemical device can be improved.
[0007] In one embodiment of the present application, 15° C. ≤ Δt ≤ 60° C. By regulating the value of Δt within the above range, the high temperature storage performance and mechanical safety performance of the electrochemical device can be further improved.
[0008] In one embodiment of the present application, the solubility of the modified melamine salt in the test electrolyte is s1, s1 < 0.1 g / g. By regulating the solubility s1 of the modified melamine salt in the test electrolyte within the above range, the modified melamine salt dissolved in the test electrolyte can be reduced, the stability of the coating composition can be improved, and thus the high temperature storage performance and mechanical safety performance of the electrochemical device can be improved.
[0009] In one embodiment of the present application, s1≤0.02 g / g. By regulating the solubility s1 of the modified melamine salt in the test electrolyte within the above range, the modified melamine salt dissolved in the test electrolyte can be further reduced, the stability of the coating composition can be improved, and the high temperature storage performance and mechanical safety performance of the electrochemical device can be further improved.
[0010] In one embodiment of the present application, the thermal weight loss mass residual rate characterized by the modified melamine salt on the thermogravimetric (TG) curve is w, 1%≤w≤35%. By regulating the thermal weight loss mass residual rate w of the modified melamine salt within the above range, the thermal stability of the modified melamine salt can be improved, and the possibility of high-temperature decomposition of the modified melamine salt can be reduced, thereby improving the high-temperature storage performance and mechanical safety performance of the electrochemical device.
[0011] In one embodiment of the present application, 4.56%≤w≤33%. By regulating the thermal weight loss residual rate w of the modified melamine salt within the above range, the high temperature storage performance and mechanical safety performance of the electrochemical device can be further improved.
[0012] In one embodiment of the present application, the particle size of the modified melamine salt is Dv50, 0.1 μm ≤ Dv50 ≤ 3 μm. By adjusting the particle size Dv50 of the modified melamine salt within the above range, the particle size of the coating composition can be moderate, the thickness and uniformity of the coating can be improved, and the high temperature storage performance and mechanical safety performance of the electrochemical device can be improved.
[0013] In one embodiment of the present application, 0.3 μm ≤ Dv50 ≤ 1.5 μm. By adjusting the value of the particle size Dv50 of the modified melamine salt within the above range, the thickness and uniformity of the coating can be further improved, thereby further improving the high temperature storage performance and mechanical safety performance of the electrochemical device.
[0014] In one embodiment of the present application, based on the mass of the coating composition, the mass percentage of the modified melamine salt is a, 50%≤a≤99%. By regulating the mass percentage a of the modified melamine salt within the above range, the modified melamine salt in the coating composition can have a suitable mass, which can reduce heat generation when problems such as overheating or impact occur, thereby improving the high temperature storage performance and mechanical safety performance of the electrochemical device.
[0015] In one embodiment of the present application, 70%≤a≤95%. By regulating the mass percentage a of the modified melamine salt within the above range, the modified melamine salt in the coating composition can have a suitable mass, and when problems such as overheating or impact occur, the movement of lithium ions and electrons in the positive electrode sheet is further restricted, making it difficult for current to flow, thereby reducing heat generation, thereby further improving the high temperature storage performance and mechanical safety performance of the electrochemical device.
[0016] In one embodiment of the present application, the binder includes at least one of polyacrylic acid, polyacrylate, polyvinylidene fluoride, styrene-butadiene rubber, sodium carboxymethyl cellulose, polyvinyl alcohol, polyimide or aluminum hydroxide sol. By regulating the type of the binder within the above range, the high temperature storage performance and mechanical safety performance of the electrochemical device can be improved.
[0017] In one embodiment of the present application, the modified melamine salt is obtained by introducing a molecular modifier during the reaction of melamine with an inorganic acid or an organic acid, wherein the molecular modifier contains multiple hydroxyl groups or multiple amino groups. By regulating the preparation method of the modified melamine salt within the scope of the present application, the modified melamine salt can have a lower endothermic temperature than the unmodified melamine salt, thereby improving the high temperature storage performance and mechanical safety performance of the electrochemical device.
[0018] In one embodiment of the present application, the molecular modifier includes a polyhydroxyl polymer polymerized from a small molecule compound, and the polyhydroxyl polymer includes at least one of polyvinyl alcohol, polyethylene glycol, or a polymerized polyol. By regulating the type of the molecular modifier within the above range, the high temperature storage performance and mechanical safety performance of the electrochemical device can be improved.
[0019] In one embodiment of the present application, the molecular modifier includes a polyhydroxy compound or a polyamino compound. The polyhydroxy compound includes at least one of ethylene glycol, propylene glycol, glycerol, butanediol, hexanediol, pentaerythritol, ethylenediaminetetraacetic acid, trimethylolethane, xylitol or sorbitol. The polyamino compound includes at least one of ethylenediamine or hexamethylenetetramine. By regulating the type of the molecular modifier within the above range, the high temperature storage performance and mechanical safety performance of the electrochemical device can be improved.
[0020] In one embodiment of the present application, the inorganic acid includes at least one of phosphoric acid, pyrophosphoric acid or boric acid, and the organic acid includes at least one of cyanuric acid, phthalic acid, oxalic acid, phytic acid or 2-carboxyethylphenylphosphinic acid. By regulating the type of inorganic acid or organic acid in the molecular modification process within the above range, the high temperature storage performance and mechanical safety performance of the electrochemical device can be improved.
[0021] In one embodiment of the present application, based on the total mass of the modified melamine salt, the mass percentage of the molecular modifier is b, 0.1%≤b≤15.0%. By regulating the mass percentage b of the molecular modifier within the above range, the molecular modifier has a suitable amount, the molecular modifier can be reacted completely, the residual molecular modifier is reduced, and the possibility of the residual molecular modifier dissolving in the electrolyte is reduced, thereby improving the high temperature storage performance and mechanical safety performance of the electrochemical device.
[0022] In one embodiment of the present application, 0.5%≤b≤5.0%. By regulating the mass percentage b of the molecular modifier within the above range, the molecular modifier can be further reacted completely, the residual molecular modifier is reduced, and the possibility of the residual molecular modifier dissolving in the electrolyte is reduced, thereby further improving the high temperature storage performance and mechanical safety performance of the electrochemical device.
[0023] In one embodiment of the present application, the absolute value of the pH difference between the modified melamine salt and the binder is m, 0≤m≤5.0. By regulating the absolute value m of the pH difference between the modified melamine salt and the binder within the above range, the pH of the binder and the modified melamine salt can be made similar, so as to improve the high temperature storage performance and mechanical safety performance of the electrochemical device.
[0024] In one embodiment of the present application, 0≤m≤2.5. By adjusting the absolute value m of the pH difference between the modified melamine salt and the binder within the above range, the high temperature storage performance and mechanical safety performance of the electrochemical device can be further improved.
[0025] The second aspect of the present application provides an electrochemical device, which comprises the coating composition in any of the above embodiments. Therefore, the electrochemical device has good high-temperature storage performance and mechanical safety performance.
[0026] In one embodiment of the present application, the electrochemical device includes a positive electrode sheet and a separator, wherein the coating composition is disposed on a surface of the separator facing the positive electrode sheet and / or on at least one surface of the positive electrode sheet.
[0027] The third aspect of the present application provides an electronic device, which includes the electrochemical device in any of the above embodiments. Therefore, the electronic device has good high-temperature storage performance and mechanical safety performance.
[0028] The present application provides a coating composition and an electrochemical device and an electronic device comprising the same. The coating composition includes a modified melamine salt and a binder, wherein the endothermic temperature characterized by the modified melamine salt on the DSC curve is lower than the endothermic temperature of the unmodified melamine acid salt, and the difference is Δt, 5°C≤Δt≤100°C. Compared with the unmodified melamine salt, the modified melamine salt has a lower endothermic temperature and can regulate the thermal decomposition temperature. By using the modified melamine salt in the coating composition and regulating Δt within the scope of the present application, the high-temperature storage performance and mechanical safety performance of the electrochemical device can be improved.
[0029] Of course, implementing any product or method of the present application does not necessarily require achieving all of the advantages described above at the same time. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application, and for ordinary technicians in this field, other embodiments can also be obtained based on these drawings.
[0031] Figure 1 is the DSC curve of the modified melamine cyanurate in Example 1-2 of the present application;
[0032] Figure 2 This is the DSC curve of the unmodified melamine cyanurate in Comparative Example 2 of the present application;
[0033] Figure 3 TG curve of the modified melamine cyanurate in Example 1-2 of the present application;
[0034] Figure 4 TG curve of unmodified melamine cyanurate in Comparative Example 2 of the present application;
[0035] Figure 5 This is a scanning electron microscope photograph of unmodified melamine cyanurate in Comparative Example 2 of the present application;
[0036] Figure 6 This is a scanning electron microscope photograph of the modified melamine cyanurate in Example 1-2 of the present application;
[0037] Figure 7 This is a scanning electron microscope photograph of the modified melamine cyanurate in Examples 1-4 of the present application. DETAILED DESCRIPTION
[0038] The following will be combined with the embodiments of the present application to clearly and completely describe the technical solutions in the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all the embodiments. All other embodiments obtained by those skilled in the art based on the present application belong to the scope of protection of the present application.
[0039] It should be noted that in the specific implementation of the present application, lithium-ion batteries are used as an example of electrochemical devices to explain the present application, but the electrochemical devices of the present application are not limited to lithium-ion batteries. The specific technical solution is as follows:
[0040] The first aspect of the present application provides a coating composition, which includes a modified melamine salt and a binder, wherein the endothermic temperature of the modified melamine salt characterized by the DSC curve is lower than the endothermic temperature of the unmodified melamine salt, and the difference is Δt, 5°C≤Δt≤100°C.
[0041] Exemplarily, Δt may be 5°C, 10°C, 20°C, 30°C, 40°C, 50°C, 60°C, 70°C, 80°C, 90°C, 100°C, or a range consisting of any two of the above values. When Δt < 5°C, the endothermic temperature difference is too small to reflect the performance difference between the modified melamine salt and the unmodified melamine salt; when Δt > 100°C, the endothermic temperature difference is too large, and the thermal stability of the modified melamine salt is poor, causing the secondary battery to decompose or react in a working environment such as high temperature (≥ 85°C) storage, thereby affecting the high temperature storage performance of the electrochemical device.
[0042] The inventors have found through research that when melamine salt is used in a coating composition, it can effectively limit the movement of lithium ions and electrons in the positive electrode sheet when the electrochemical device is subjected to heat exposure, penetration, collision, impact, etc., thereby making it difficult for the current to flow, effectively suppressing the overheating and explosion of the electrochemical device, and having little effect on the normal working performance of the electrochemical device. On this basis, the inventors have molecularly modified the melamine salt in the coating composition, and the endothermic temperature characterized by the modified melamine salt on the DSC curve is lower than the endothermic temperature of the unmodified melamine salt. When the difference Δt satisfies 5°C≤Δt≤100°C, the modified melamine salt has a lower endothermic temperature than the unmodified melamine salt, and can regulate the thermal decomposition temperature, thereby improving the high temperature storage performance and mechanical safety performance of the electrochemical device.
[0043] The present application has no particular restrictions on the types of modified melamine salts, as long as the purpose of the present application can be achieved. For example, the modified melamine salts include but are not limited to at least one of modified melamine phosphates, modified melamine cyanurates or modified melamine phthalates. It should be noted that "Δt" in the present application refers to the difference between the endothermic temperature of the same melamine salt after modification and the endothermic temperature of the unmodified melamine salt. Exemplarily, in some embodiments, Δt refers to the difference between the endothermic temperature of the modified melamine phosphate and the endothermic temperature of the unmodified melamine phosphate.
[0044] In one embodiment of the present application, 15°C≤Δt≤60°C. For example, Δt can be 15°C, 20°C, 25°C, 30°C, 35°C, 40°C, 45°C, 50°C, 55°C, 60°C, or a range consisting of any two of the above values. By regulating the value of Δt within the above range, the modified melamine salt can have better high temperature storage performance and mechanical safety performance.
[0045] The present application has no particular restrictions on the regulation method of Δt, as long as the purpose of the present application can be achieved. For example, the value of Δt can be regulated by changing the type and / or mass percentage of the introduced molecular modifier during the synthesis of the modified melamine salt, or by introducing the molecular modifier at different stages of the synthesis of the modified melamine salt. Generally, Δt will be different depending on the type and / or mass percentage of the molecular modifier. For example, as the mass percentage of the molecular modifier increases, Δt increases.
[0046] In one embodiment of the present application, the solubility of the modified melamine salt in the test electrolyte is s1, s1 < 0.1g / g. Exemplarily, the value of s1 can be 0.01g / g, 0.02g / g, 0.03g / g, 0.04g / g, 0.05g / g, 0.06g / g, 0.07g / g, 0.08g / g, 0.09g / g or a range consisting of any two of the above values. By regulating the solubility s1 of the modified melamine salt in the test electrolyte within the above range, the modified melamine salt dissolved in the test electrolyte can be reduced, the stability of the coating composition can be improved, and the high temperature storage performance and mechanical safety performance of the electrochemical device can be improved.
[0047] In the present application, the preparation method of the test electrolyte may include but is not limited to the following steps: ethylene carbonate, propylene carbonate (PC) and diethyl carbonate (DEC) are mixed in a mass ratio of (15% to 25%): (25% to 35%): (55% to 65%) as a base solvent, lithium salt LiPF6, carboxylic acid ester and fluoroethylene carbonate are mixed and added to the base solvent, and stirred evenly to obtain a test electrolyte. Wherein, based on the mass of the test electrolyte, the mass percentage of lithium salt LiPF6 can be 10% to 20%, the mass percentage of carboxylic acid ester and fluoroethylene carbonate can be 2% to 15% respectively, and the remainder is the base solvent. The above-mentioned carboxylic acid ester includes but is not limited to at least one of methyl formate, methyl acetate, ethyl acetate, n-propyl acetate, tert-butyl acetate, methyl propionate, ethyl propionate, propyl propionate, γ-butyrolactone, decalactone, valerolactone or caprolactone.
[0048] In one embodiment of the present application, the solubility of the modified melamine salt in the test electrolyte is s1, s1≤0.02g / g. Exemplarily, the value of s1 can be 0.001g / g, 0.005g / g, 0.01g / g, 0.015g / g, 0.02g / g, or a range consisting of any two of the above values. By regulating the solubility s1 of the modified melamine salt in the test electrolyte within the above range, the modified melamine salt dissolved in the test electrolyte is further reduced, the stability of the coating composition is improved, and the high temperature storage performance and mechanical safety performance of the electrochemical device are further improved.
[0049] The present application has no particular restrictions on the method for regulating the solubility of the modified melamine salt in the test electrolyte, as long as the purpose of the present application can be achieved. For example, it can be achieved by regulating at least one of the reaction temperature, reaction time or cleaning and drying process during the synthesis of the modified melamine salt.
[0050] In one embodiment of the present application, the thermal weight loss residual rate of the modified melamine salt characterized on the thermogravimetric curve is w, 1%≤w≤35%. Exemplarily, the value of w can be 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29%, 30%, 31%, 32%, 33%, 34%, 35% or a range consisting of any two of the above values. Unmodified melamine salt will decompose and sublime in a temperature environment greater than or equal to 250°C, and modified melamine salt will be carbonized and retained on the positive electrode sheet and / or the diaphragm after being treated at a temperature greater than or equal to 250°C. By regulating the thermal weight loss mass residual rate w of the modified melamine salt within the above range, the thermal response starting temperature and response rate of the modified melamine salt can be increased, so that when the electrochemical device generates heat rapidly, the modified melamine salt will decompose when exposed to heat, absorb heat to reduce the temperature, generate gas to dilute the active oxygen, and reduce the possibility of thermal runaway of the electrochemical device. At the same time, the product of the carbonized modified melamine salt can maintain the coating structure, reducing the possibility of further contact and short circuit between the positive electrode sheet and the negative electrode sheet. Thereby improving the high temperature storage performance and mechanical safety performance of the electrochemical device.
[0051] In one embodiment of the present application, 4.56%≤w≤33%. Exemplarily, the value of w can be 4.56%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29%, 30%, 31%, 32%, 33% or a range consisting of any two of the above values. By regulating the thermal weight loss mass residual rate w of the modified melamine salt within the above range, the thermal stability of the modified melamine salt can be further improved, thereby further improving the high temperature storage performance and mechanical safety performance of the electrochemical device.
[0052] The present application has no particular restrictions on the control method of the thermal weight loss residual mass rate w of the modified melamine salt, as long as the purpose of the present application can be achieved. For example, it can be achieved by changing at least one of the type or mass percentage of the introduced molecular modifier during the synthesis of the modified melamine salt. Generally, w will be different depending on the type and / or mass percentage of the molecular modifier.
[0053] In one embodiment of the present application, the particle size of the modified melamine salt is Dv50, 0.1 μm ≤ Dv50 ≤ 3.0 μm. For example, the value of Dv50 can be 0.1 μm, 0.2 μm, 0.3 μm, 0.4 μm, 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm, 1.0 μm, 1.1 μm, 1.2 μm, 1.3 μm, 1.4 μm, 1.5 μm, 1.6 μm, 1.7 μm, 1.8 μm, 1.9 μm, 2.0 μm, 2.1 μm, 2.2 μm, 2.3 μm, 2.4 μm, 2.5 μm, 2.6 μm, 2.7 μm, 2.8 μm, 2.9 μm, 3.0 μm, or a range consisting of any two of the above values. By regulating the particle size Dv50 of the modified melamine salt within the above range, the particle size of the coating composition can be moderate, and the thickness and uniformity of the coating formed by the coating composition can be improved, thereby improving the high temperature storage performance and mechanical safety performance of the electrochemical device.
[0054] In one embodiment of the present application, 0.3 μm ≤ Dv50 ≤ 1.5 μm. Exemplarily, Dv50 may be 0.3 μm, 0.4 μm, 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm, 1.0 μm, 1.1 μm, 1.2 μm, 1.3 μm, 1.4 μm, 1.5 μm, or a range consisting of any two of the above values. By regulating the value of the particle size Dv50 of the modified melamine salt within the above range, the thickness and uniformity of the coating formed by the coating composition can be further improved, thereby further improving the high temperature storage performance and mechanical safety performance of the electrochemical device.
[0055] The present application has no particular restrictions on the method for controlling the particle size Dv50 of the modified melamine salt, as long as the purpose of the present application can be achieved. For example, it can be achieved by screening or crushing.
[0056] In the present application, the particle size Dv50 of the modified melamine salt refers to a particle size at which the volume accumulation is 50% from the smaller particle size side in the volume-based particle size distribution of the modified melamine salt particles.
[0057] In one embodiment of the present application, based on the mass of the coating composition, the mass percentage of the modified melamine salt is a, 50%≤a≤99%. Exemplarily, the value of a can be 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90%, 95%, 99% or a range consisting of any two of the above values. By regulating the mass percentage a of the modified melamine salt within the above range, the modified melamine salt in the coating composition can have a suitable mass, and when problems such as overheating or impact occur, the movement of lithium ions and electrons in the positive electrode sheet can be better limited. In this way, it is possible to make the flow of current difficult, reduce heat generation, and thus improve the high temperature storage performance and mechanical safety performance of the electrochemical device.
[0058] In one embodiment of the present application, 70%≤a≤95%. Exemplarily, a can be 70%, 71%, 72%, 73%, 74%, 75%, 76%, 77%, 78%, 79%, 80%, 81%, 82%, 83%, 84%, 85%, 86%, 87%, 88%, 89%, 90%, 91%, 92%, 93%, 94%, 95% or a range consisting of any two of the above values. By regulating the mass percentage a of the modified melamine salt within the scope of the present application, the modified melamine salt in the coating composition can have a suitable mass, and when problems such as overheating or impact occur, the movement of lithium ions and electrons in the positive electrode sheet is further restricted, making it difficult for current to flow, thereby reducing heat generation, thereby further improving the high temperature storage performance and mechanical safety performance of the electrochemical device.
[0059] In one embodiment of the present application, the binder includes at least one of polyacrylic acid, polyacrylate, polyvinylidene fluoride, styrene-butadiene rubber, sodium carboxymethyl cellulose, polyvinyl alcohol, polyimide or aluminum hydroxide sol. By regulating the type of the binder within the scope of the present application, the bonding force between the coating composition and the positive electrode current collector can be improved, the degree of peeling between the coating composition and the positive electrode current collector during the cycle can be reduced, and the interface contact impedance during the cycle can be improved, thereby improving the high temperature storage performance and mechanical safety performance of the electrochemical device.
[0060] The present application has no particular limitation on the mass percentage of the binder in the coating composition, as long as the purpose of the present application can be achieved. For example, based on the mass of the coating composition, the mass percentage of the binder is 1% to 10%.
[0061] In one embodiment of the present application, the coating composition further includes a ceramic compound. The present application has no particular restrictions on the type of the ceramic compound, as long as the purpose of the present application can be achieved. For example, the ceramic compound may include at least one of an inorganic fast ion conductor, magnesium hydroxide, aluminum hydroxide, silicon dioxide, aluminum oxide or boehmite. Among them, the inorganic fast ion conductor may include lithium aluminum titanium phosphate (Li 1+a Al a Ti 2-a (PO4)3, 0.1≤a≤0.5, abbreviated as LATP), lithium lanthanum titanium oxide (Li 3b La (2 / 3-b) TiO3, 0.03 ≤ b ≤ 0.167, abbreviated as LLTO) or lithium lanthanum zirconium oxide (Li7La3Zr2O 12 , abbreviated as LLZO). The present application has no particular limitation on the type of ceramic compound, as long as the purpose of the present application can be achieved. For example, based on the mass of the coating composition, the mass percentage of the ceramic compound is 0% to 50%.
[0062] In one embodiment of the present application, the coating composition further includes a wetting agent. The present application does not particularly limit the type of the wetting agent, and conventional wetting agents known in the art can be selected as long as the purpose of the present application can be achieved. The present application does not particularly limit the content of the wetting agent, as long as the purpose of the present application can be achieved. For example, based on the mass of the coating composition, the mass percentage of the wetting agent is 0% to 2%.
[0063] In one embodiment of the present application, the modified melamine salt is obtained by introducing a molecular modifier during the reaction of melamine with an inorganic acid or an organic acid, and the molecular modifier contains multiple hydroxyl groups or multiple amino groups. It should be noted that the above-mentioned "multiple" refers to 2 or more hydroxyl groups or amino groups. The present application does not particularly limit the number of hydroxyl groups and amino groups in the molecular modifier, as long as the purpose of the present application can be achieved. For example, the number of hydroxyl or amino functional groups can be 2 to 4. By introducing a molecular modifier during the hydrogen bond self-assembly process of the reaction of melamine with an inorganic acid or an organic acid, so that it participates in the hydrogen bond self-assembly process of the melamine salt, destroying its planar regularity at the supramolecular level, interfering with the formation of a uniform large planar hydrogen bond network, thereby reducing the melting temperature. The preparation method of the modified melamine salt is regulated within the scope of the present application, so that the modified melamine salt can have an endothermic temperature difference within the scope of the present application compared to the unmodified melamine salt, thereby improving the high temperature storage performance and mechanical safety performance of the electrochemical device.
[0064] The present application has no particular restrictions on the method for preparing the coating composition, as long as the purpose of the present application can be achieved. For example, in some embodiments, the method for preparing the coating composition includes but is not limited to the following steps: (1) Preparation of modified melamine salt: obtained by introducing a molecular modifier during the reaction of melamine with an inorganic acid or an organic acid. (2) Preparation of the coating composition: In a dispersion tank, add the above-mentioned modified melamine salt, a binder and a ceramic compound, add a solvent, disperse and mix evenly, and obtain a coating composition. The present application has no particular restrictions on the type of solvent in the above step (2), as long as the purpose of the present application can be achieved. For example, the solvent includes but is not limited to N-methylpyrrolidone (NMP) or deionized water.
[0065] In one embodiment of the present application, the molecular modifier includes a polyhydroxyl polymer polymerized from a small molecule compound, and the polyhydroxyl polymer includes polyvinyl alcohol (HO(CHCHO) n H), polyethylene glycol (HO(CH2CH2O) n H), or at least one of polymerized polyols. In polyvinyl alcohol, n is the degree of polymerization, which is divided into ultra-high degree of polymerization (molecular weight 250,000 to 300,000), high degree of polymerization (molecular weight 170,000 to 220,000), medium degree of polymerization (molecular weight 120,000 to 150,000) and low degree of polymerization (molecular weight 25,000 to 35,000). The relative molecular mass of polyethylene glycol is 200 to 6000, and it can be used as a melting agent. The present application does not particularly limit the type of polymerized polyol, as long as the purpose of the present application can be achieved. For example, the polymerized polyol can be polypropylene glycol (H(C3H6O)) with a molecular weight of 400 to 2000. n OH) or propylene glycol homopolymer with a molecular weight of 200 to 1500 (HO(CH2OHCHCH2O) n By adjusting the type of the molecular modifier within the above range, the modified melamine salt can have different endothermic temperatures, thereby improving the high temperature storage performance and mechanical safety performance of the electrochemical device.
[0066] In one embodiment of the present application, the molecular modifier includes a polyhydroxy compound or a polyamino compound. The polyhydroxy compound includes at least one of ethylene glycol, propylene glycol, glycerol, butanediol, hexanediol, pentaerythritol, ethylenediaminetetraacetic acid, trimethylolethane, xylitol or sorbitol. The polyamino compound includes at least one of ethylenediamine or hexamethylenetetramine. By regulating the type of the molecular modifier within the above range, the modified melamine salt can have different endothermic temperatures, thereby improving the high temperature storage performance and mechanical safety performance of the electrochemical device.
[0067] In one embodiment of the present application, the inorganic acid includes at least one of phosphoric acid, pyrophosphoric acid or boric acid, and the organic acid includes at least one of cyanuric acid, phthalic acid, oxalic acid, phytic acid or 2-carboxyethylphenylphosphinic acid. By regulating the type of inorganic acid or organic acid in the molecular modification process within the above range, the modified melamine salt can have different endothermic temperatures, thereby improving the high temperature storage performance and mechanical safety performance of the electrochemical device.
[0068] In one embodiment of the present application, based on the total mass of the modified melamine salt, the mass percentage of the molecular modifier is b, 0.1%≤b≤15.0%. Exemplarily, the value of b can be 0.1%, 0.5%, 1.0%, 1.5%, 2.0%, 2.5%, 3.0%, 3.5%, 4.0%, 4.5%, 5.0%, 5.5%, 6.0%, 6.5%, 7.0%, 7.5%, 8.0%, 8.5%, 9.0%, 9.5%, 10.0%, 10.5%, 11.0%, 11.5%, 12.0%, 12.5%, 13.0%, 14.5%, 15.0% or a range consisting of any two of the above values. By regulating the mass percentage b of the molecular modifier within the above range, the molecular modifier has an appropriate amount. During the synthesis of the modified melamine salt, the molecular modifier has a low probability of destroying the structure of the melamine salt. The molecular modifier forms a bond with the melamine salt molecule and reacts completely, thereby reducing the probability of the molecular modifier existing in the reaction system as a pure substance. In this way, the prepared modified melamine salt has a suitable endothermic temperature difference compared to the same type of unmodified melamine salt. As a result, the high temperature storage performance and mechanical safety performance of the electrochemical device can be improved.
[0069] In one embodiment of the present application, 0.5%≤b≤5.0%. Exemplarily, the value of b can be 0.5%, 1.0%, 1.5%, 2.0%, 2.5%, 3.0%, 3.5%, 4.0%, 4.5%, 5.0% or a range consisting of any two of the above values. By regulating the value of the mass percentage b of the molecular modifier within the above range, the molecular modifier can be further reacted with the melamine salt completely, reducing the probability that the molecular modifier exists in the reaction system as a pure substance. In this way, the prepared modified melamine salt has a suitable endothermic temperature difference compared to the same type of unmodified melamine salt. Thus, the high temperature storage performance and mechanical safety performance of the electrochemical device can be further improved.
[0070] In one embodiment of the present application, the absolute value of the pH difference between the modified melamine salt and the binder is m, 0≤m≤5.0. Exemplarily, the value of m can be 0, 0.5, 1.0, 1.5, 2.0, 2.5, 3.0, 3.5, 4.0, 4.5, 5.0 or a range consisting of any two of the above values. By regulating the absolute value m of the pH difference between the modified melamine salt and the binder within the above range, the difference between the pH of the binder and the modified melamine salt can be reduced, and the possibility of the binder and the modified melamine salt agglomerating to produce large particles during the stirring and mixing of the slurry due to acid-base imbalance can be reduced, so that the binder is evenly dispersed, and the generation of problems such as missing coating, clogging and over-thickness during the coating process is reduced, and the transmission capacity of lithium ions and electrons in the coating composition is improved, thereby improving the high temperature storage performance and mechanical safety performance of the electrochemical device.
[0071] In one embodiment of the present application, 0≤m≤2.5. Exemplarily, the value of m can be 0, 0.5, 1.0, 1.5, 2.0, 2.5 or a range consisting of any two of the above values. By regulating the absolute value m of the pH difference between the modified melamine salt and the binder within the above range, the difference in pH between the binder and the modified melamine salt can be further reduced, and the acid-base imbalance can be further reduced to cause the binder and the modified melamine salt to agglomerate and produce large particles during the stirring and mixing of the slurry, thereby reducing the possibility of problems such as missing coating, blockage and over-thickness caused by large particles during the coating process, and at the same time, the possibility of obstruction of the transmission of lithium ions and electrons due to large particles can be reduced. Thereby further improving the high temperature storage performance and mechanical safety performance of the electrochemical device.
[0072] The present application has no particular restrictions on the method for regulating the absolute value m of the pH difference, as long as the purpose of the present application can be achieved. For example, it can be achieved by mixing the same modified melamine salt with different types of binders or by mixing the same binder with modified melamine salts of different pH values.
[0073] A second aspect of the present application provides an electrochemical device, which includes the coating composition in any of the aforementioned embodiments. Therefore, the electrochemical device has good high-temperature storage performance and mechanical safety performance.
[0074] In one embodiment of the present application, the electrochemical device further includes a positive electrode sheet and a diaphragm, and the coating composition is disposed on the surface of the diaphragm facing the positive electrode sheet and / or on at least one surface of the positive electrode sheet. For example, in some embodiments, the coating composition may be disposed on a surface of the diaphragm facing the positive electrode sheet along its own thickness direction. In other embodiments, the coating composition is disposed on a surface of the diaphragm facing the positive electrode sheet along its own thickness direction, and the coating composition is also disposed on a surface of the positive electrode sheet along its own thickness direction. In some further embodiments, the coating composition is disposed on a surface of the diaphragm facing the positive electrode sheet along its own thickness direction, and at the same time, the coating composition is also disposed on two surfaces of the positive electrode sheet along its own thickness direction. It should be noted that the "surface" here can be the entire area of the surface of the positive electrode sheet or the diaphragm, or it can be a partial area of the surface of the positive electrode sheet or the diaphragm. This application is not particularly limited as long as the purpose of this application can be achieved.
[0075] In the present application, the positive electrode plate includes a positive electrode current collector and a positive electrode material layer disposed on at least one surface of the positive electrode current collector. The above-mentioned "positive electrode material layer disposed on at least one surface of the positive electrode current collector" means that the positive electrode material layer can be disposed on one surface of the positive electrode current collector along its own thickness direction, or it can be disposed on two surfaces of the positive electrode current collector along its own thickness direction. It should be noted that the "surface" here can be the entire area of the surface of the positive electrode current collector, or it can be a partial area of the surface of the positive electrode current collector. This application has no special restrictions, as long as the purpose of this application can be achieved. This application has no special restrictions on the positive electrode current collector, as long as the purpose of this application can be achieved. For example, it can include aluminum foil, aluminum alloy foil or a composite current collector (such as an aluminum-carbon composite current collector). The positive electrode material layer includes a positive electrode active material. The present application has no particular restrictions on the positive electrode active material, as long as the purpose of the present application can be achieved. For example, the positive electrode active material may include but is not limited to lithium nickel cobalt manganese oxide (such as NCM811, NCM622, NCM523, NCM111), lithium nickel cobalt aluminum oxide, lithium iron phosphate, lithium-rich manganese-based materials, lithium cobalt oxide (LiCoO2), lithium manganese oxide, lithium iron manganese phosphate or lithium titanate. The positive electrode material layer may also include a conductive agent and a positive electrode binder. The present application has no particular restrictions on the conductive agent and the positive electrode binder, as long as the purpose of the present application can be achieved. For example, the conductive agent may include but is not limited to at least one of conductive carbon black (Super P), carbon nanotubes (CNTs), carbon fibers, flake graphite, graphene, metal materials or conductive polymers, and the conductive carbon black may include but is not limited to at least one of acetylene black or Ketjen black. The above-mentioned carbon nanotubes may include but are not limited to single-walled carbon nanotubes and / or multi-walled carbon nanotubes. The above-mentioned carbon fibers may include but are not limited to vapor-grown carbon fibers (VGCF) and / or nanocarbon fibers. The above-mentioned metal material may include but is not limited to metal powder and / or metal fiber. Specifically, the metal may include but is not limited to at least one of copper, nickel, aluminum or silver. The above-mentioned conductive polymer may include but is not limited to at least one of polyphenylene derivatives, polyaniline, polythiophene, polyacetylene or polypyrrole. The positive electrode binder may include but is not limited to at least one of polyacrylic acid, sodium polyacrylate, potassium polyacrylate, lithium polyacrylate, polyimide, polyvinyl alcohol, carboxymethyl cellulose, sodium carboxymethyl cellulose, lithium carboxymethyl cellulose, polyimide, polyamide-imide, styrene-butadiene rubber or polyvinylidene fluoride. The present application has no particular restrictions on the thickness of the positive electrode collector and the positive electrode material layer, as long as the purpose of the present application can be achieved. For example, the thickness of the positive electrode collector is 5μm to 20μm, and the thickness of the positive electrode material layer is 30μm to 120μm. Optionally, the positive electrode sheet may also include a conductive layer, which is located between the positive electrode collector and the positive electrode material layer. The composition of the conductive layer is not particularly limited and may be a conductive layer commonly used in the art. The conductive layer includes a conductive agent and a positive electrode binder.The present application has no particular limitation on the conductive agent and the positive electrode binder in the conductive layer. For example, the conductive layer may be at least one of the above conductive agent and the above positive electrode binder.
[0076] The present application has no particular restrictions on the diaphragm, as long as the purpose of the present application can be achieved. For example, in one embodiment of the present application, the material of the diaphragm may include, but is not limited to, polyethylene (PE), polypropylene (PP)-based polyolefins (PO), polyesters (e.g., polyethylene terephthalate (PET) films), cellulose, polyimide (PI), polyamide (PA), spandex, or aramid. The type of diaphragm may include at least one of a woven membrane, a nonwoven membrane, a microporous membrane, a composite membrane, a rolled membrane, or a spun membrane.
[0077] In one embodiment of the present application, the diaphragm may include a substrate and a surface treatment layer. The substrate may be a non-woven fabric or a composite film having a porous structure, and the material of the substrate may include at least one of polyethylene, polypropylene, polyethylene terephthalate or polyimide. Optionally, a polypropylene porous film, a polyethylene porous film, a polypropylene non-woven fabric, a polyethylene non-woven fabric or a polypropylene-polyethylene-polypropylene porous composite film may be used. Optionally, a surface treatment layer is provided on at least one surface of the substrate, and the surface treatment layer may be a polymer layer or an inorganic layer, or a layer formed by a mixed polymer and an inorganic substance. In some embodiments of the present application, the inorganic layer includes inorganic particles and a diaphragm binder. The present application has no particular restrictions on inorganic particles, for example, inorganic particles may include at least one of aluminum oxide, silicon oxide, magnesium oxide, titanium oxide, hafnium dioxide, tin oxide, cerium dioxide, nickel oxide, zinc oxide, calcium oxide, zirconium oxide, yttrium oxide, silicon carbide, boehmite, aluminum hydroxide, magnesium hydroxide, calcium hydroxide or barium sulfate. The present application has no particular restrictions on the separator binder, for example, the separator binder can be at least one of the above-mentioned positive electrode binders. In some embodiments of the present application, the polymer layer includes a polymer, and the polymer material includes at least one of polyamide, polyacrylonitrile, acrylate polymer, polyacrylic acid, polyacrylate, polyvinyl pyrrolidone, polyvinyl ether or polyvinylidene fluoride or poly (vinylidene fluoride-hexafluoropropylene). In the present application, the thickness of the separator is not particularly limited, as long as the purpose of the present application can be achieved.
[0078] The present application has no particular restrictions on the preparation method of the positive electrode sheet, as long as the purpose of the present application can be achieved. For example, in some embodiments, the two surfaces of the positive electrode sheet are provided with a coating composition, and the preparation method of the positive electrode sheet may include but is not limited to the following steps: (1) Preparation of semi-finished positive electrode sheet: Add the positive electrode active material, the conductive agent, and the positive electrode binder to N-methylpyrrolidone, stir and mix evenly to form a positive electrode slurry, evenly apply the positive electrode slurry to one side of the positive electrode collector and then dry it, and then repeat the above steps on the other side of the positive electrode collector to obtain a semi-finished positive electrode sheet coated with a positive electrode material layer on both sides. (2) Preparation of positive electrode sheet: Apply the coating composition to the surface of the positive electrode material layer on one side of the semi-finished positive electrode sheet away from the positive electrode collector by gravure roller transfer coating, and then repeat the above steps on the surface of the positive electrode material layer on the other side of the semi-finished positive electrode sheet away from the positive electrode collector, and dry it to obtain a positive electrode sheet. For example, in some other embodiments, the positive electrode sheet has only one surface provided with a coating composition, and the preparation method of the positive electrode sheet may include but is not limited to the following steps: (1) Preparation of semi-finished positive electrode sheet: Add the positive electrode active material, the conductive agent, and the positive electrode binder into N-methylpyrrolidone, stir and mix evenly to form a positive electrode slurry, evenly apply the positive electrode slurry to one side of the positive electrode current collector and then dry, and then repeat the above steps on the other side of the positive electrode current collector to obtain a semi-finished positive electrode sheet with a positive electrode material layer coated on both sides. (2) Preparation of positive electrode sheet: Select any side of the semi-finished positive electrode sheet with a positive electrode material layer coated on both sides, apply the coating composition to the side of the positive electrode material layer away from the positive electrode current collector by gravure roller transfer coating, and dry to obtain a positive electrode sheet. For example, in some further embodiments, the preparation method of the positive electrode sheet may include but is not limited to the following steps: adding the positive electrode active material, the conductive agent, and the positive electrode binder to N-methylpyrrolidone, stirring and mixing evenly to form a positive electrode slurry, evenly coating the positive electrode slurry on one side of the positive electrode collector and drying it, and then repeating the above steps on the other side of the positive electrode collector to obtain a positive electrode sheet coated with a positive electrode material layer on both sides.
[0079] The present application has no particular restrictions on the mass ratio of the positive electrode active material, the conductive agent, and the positive electrode binder, as long as the purpose of the present application can be achieved. For example, the mass ratio of the positive electrode active material, the conductive agent, and the positive electrode binder can be (95 to 98): (1 to 5): (1 to 3). The present application has no particular restrictions on the solid content of the positive electrode slurry, as long as the purpose of the present application can be achieved. The present application has no particular restrictions on the above-mentioned drying temperature, as long as the purpose of the present application can be achieved. For example, the drying temperature can be 90°C to 130°C.
[0080] The present application has no particular restrictions on the preparation method of the diaphragm, as long as the purpose of the present application can be achieved. For example, in some embodiments, a coating composition is provided on the surface of the diaphragm facing the positive electrode sheet, and the preparation method of the diaphragm may include but is not limited to the following steps: preparing a substrate, applying the coating composition to the surface of the substrate facing the positive electrode sheet by gravure roller transfer coating, and drying in an oven at 45°C to 60°C to obtain a diaphragm. The above-mentioned substrate can also be purchased.
[0081] In the present application, the electrochemical device also includes a negative electrode plate, which includes a negative electrode current collector and a negative electrode material layer disposed on at least one surface of the negative electrode current collector. The above-mentioned "negative electrode material layer disposed on at least one surface of the negative electrode current collector" means that the negative electrode material layer can be disposed on one surface of the negative electrode current collector along its own thickness direction, or it can be disposed on two surfaces of the negative electrode current collector along its own thickness direction. It should be noted that the "surface" here can be the entire area of the surface of the negative electrode current collector, or it can be a partial area of the surface of the negative electrode current collector. This application has no special restrictions, as long as the purpose of this application can be achieved. This application has no special restrictions on the negative electrode current collector, as long as the purpose of this application can be achieved. For example, it can include copper foil, copper alloy foil, nickel foil, stainless steel foil, titanium foil, foam nickel, foam copper or a composite current collector. For example, the composite current collector can be a lithium-copper composite current collector, a carbon-copper composite current collector, a nickel-copper composite current collector, a titanium-copper composite current collector, etc. The negative electrode material layer includes a negative electrode active material. The present application has no particular limitation on the negative electrode active material as long as the purpose of the present application can be achieved. For example, the negative electrode active material may include but is not limited to natural graphite, artificial graphite, mesophase microcarbon beads, hard carbon, soft carbon, silicon, silicon-carbon composite, Li-Sn alloy, Li-Sn-O alloy, Sn, SnO, SnO2, spinel structured lithiated TiO2-Li4Ti5O 12or at least one of Li-Al alloy. In some embodiments of the present application, the negative electrode material layer may further include a conductive agent and a negative electrode binder. The present application has no particular restrictions on the types of the conductive agent and the negative electrode binder, as long as the purpose of the present application can be achieved. For example, it may be at least one of the above conductive agent and the above positive electrode binder. The present application has no particular restrictions on the mass ratio of the negative electrode active material, the conductive agent, and the negative electrode binder in the negative electrode material layer. Those skilled in the art may select according to actual needs, as long as the purpose of the present application can be achieved. The present application has no particular restrictions on the thickness of the negative electrode material layer, as long as the purpose of the present application can be achieved. For example, the thickness of the single-sided negative electrode material layer is 30 μm to 120 μm. The present application has no particular restrictions on the thickness of the negative electrode current collector, as long as the purpose of the present application can be achieved. For example, the thickness of the negative electrode current collector is 4 μm to 15 μm. Optionally, the negative electrode sheet may further include a conductive layer, which is located between the negative electrode current collector and the negative electrode material layer. The present application has no particular restrictions on the composition of the conductive layer, which may be a conductive layer commonly used in the art. For example, the conductive layer includes a conductive agent and a negative electrode binder. The present application has no particular limitation on the conductive agent and the negative electrode binder in the conductive layer. For example, the conductive agent may be at least one of the above conductive agent and the above negative electrode binder.
[0082] In the present application, the electrochemical device also includes an electrolyte, and the electrolyte includes a lithium salt and a non-aqueous solvent. The present application has no particular restrictions on the lithium salt, as long as the purpose of the present application can be achieved. For example, the lithium salt may include but is not limited to at least one of LiPF6, LiBF4, LiAsF6, LiClO4, LiB(C6H5)4, LiCH3SO3, LiCF3SO3, LiN(SO2CF3)2, LiC(SO2CF3)3, Li2SiF6, lithium bis(oxalatoborate) (LiBOB) or lithium difluoroborate. The present application has no particular restrictions on the content of the lithium salt in the electrolyte, as long as the purpose of the present application can be achieved. In the present application, the non-aqueous solvent includes ethylene carbonate, carboxylic acid ester compounds and fluoroethylene carbonate (FEC) compounds. The carboxylate compound may include, but is not limited to, at least one of methyl formate, methyl acetate, ethyl acetate, n-propyl acetate, tert-butyl acetate, methyl propionate, ethyl propionate, propyl propionate, γ-butyrolactone, decanoic acid, valerolactone or caprolactone. The present application has no particular restrictions on the content of the non-aqueous solvent in the electrolyte, as long as the purpose of the present application can be achieved.
[0083] The electrochemical device of the present application also includes a packaging bag for containing a positive electrode sheet, a separator, a negative electrode sheet and an electrolyte, as well as other components known in the art in the electrochemical device, and the present application does not limit the above other components. The present application does not specifically limit the packaging bag, and it can be a packaging bag known in the art, as long as it can achieve the purpose of the present application.
[0084] The present application does not particularly limit the type of electrochemical device, which may include any device that undergoes an electrochemical reaction. In the present application, the electrochemical device may include, but is not limited to: a lithium metal secondary battery, a lithium ion secondary battery (lithium ion battery), a lithium polymer secondary battery or a lithium ion polymer secondary battery (lithium ion polymer battery), etc.
[0085] The preparation process of the electrochemical device of the present application is well known to those skilled in the art, and there is no particular limitation in the present application. For example, the preparation process of the electrochemical device may include but is not limited to the following steps: stacking the diaphragm, the positive electrode sheet, the diaphragm and the negative electrode sheet in order, and winding, folding and other operations as needed to obtain an electrode assembly of a wound structure, placing the electrode assembly in a packaging bag, injecting the electrolyte into the packaging bag and sealing it to obtain an electrochemical device. Alternatively, the diaphragm, the positive electrode sheet, the diaphragm and the negative electrode sheet are stacked in order, and then the four corners of the entire stacked structure are fixed with tape to obtain an electrode assembly of a stacked structure, placing the electrode assembly in a packaging bag, injecting the electrolyte into the packaging bag and sealing it to obtain an electrochemical device. In addition, overcurrent protection elements, guide plates, etc. may also be placed in the packaging bag as needed to prevent the pressure inside the electrochemical device from rising and overcharging and discharging.
[0086] The third aspect of the present application provides an electronic device, which includes the electrochemical device in any of the above embodiments. Therefore, the electronic device has good high-temperature storage performance and mechanical safety performance.
[0087] The present application does not particularly limit the type of electronic device, and it can be used for any electronic device known in the prior art. In some embodiments of the present application, the electronic device may include, but is not limited to, a laptop computer, a pen-input computer, a mobile computer, an electronic book player, a portable phone, a portable fax machine, a portable copier, a portable printer, a head-mounted stereo headset, a video recorder, a liquid crystal television, a portable cleaner, a portable CD player, a mini-disc, a transceiver, an electronic notepad, a calculator, a memory card, a portable recorder, a radio, a backup power supply, a motor, a car, a motorcycle, a power-assisted bicycle, a bicycle, a lighting fixture, a toy, a game console, a clock, an electric tool, a flashlight, a camera, a large household battery and a lithium-ion capacitor, etc.
[0088] Example
[0089] Hereinafter, the embodiments of the present application will be described in more detail with reference to Examples and Comparative Examples. Various tests and evaluations were performed according to the following methods.
[0090] Test methods and equipment:
[0091] Endothermic temperature test:
[0092] After the lithium-ion battery is discharged to 3.0V at a constant current of 0.1C, the lithium-ion battery is disassembled to obtain a positive electrode plate with a coating. The positive electrode plate is cleaned with N-methylpyrrolidone, and the modified melamine salt is separated from the positive electrode plate, filtered and dried at 85°C to obtain the modified melamine salt. The endothermic temperature of the modified melamine salt is measured by a differential scanning calorimeter. The endothermic temperature of the unmodified melamine salt can be obtained by directly purchasing the unmodified melamine salt of the same type and measuring it using the above-mentioned differential scanning calorimeter. Δt is the endothermic temperature difference of the unmodified melamine salt minus the modified melamine salt.
[0093] It should be noted that the above-mentioned "coating" refers to a coating containing a coating composition, and the "coating" appearing hereinafter also refers to a coating containing a coating composition.
[0094] Thermal weight loss mass residual rate test:
[0095] After the lithium-ion battery is discharged to 3.0V at a constant current of 0.1C, the lithium-ion battery is disassembled to obtain a positive electrode plate with a coating, and the coating is scraped off to obtain a coating powder. The obtained coating powder is soaked and washed with NMP solution 2 to 3 times to remove the residual lithium salt and glue layer, and then placed in a vacuum oven at 80°C to dry and remove the solvent. 5mg to 15mg of powder is spread flat in the crucible of the thermogravimetric analyzer. During the program heating process, the mass change of the sample is continuously measured with a balance. The test temperature range is from room temperature to 600°C. The test atmosphere is set in a nitrogen (N2) atmosphere.
[0096] Scanning electron microscope test:
[0097] After the lithium-ion battery was discharged to 3.0V at a constant current of 0.1C, the lithium-ion battery was disassembled to obtain a coated positive electrode sheet with a length and width of 20mm×20mm. NMP solution was dripped onto the surface of the coated positive electrode sheet to clean the lithium salt, and then dried in a forced air oven at 80°C. The positive electrode sheet was cut to obtain a test sample with a specification of 5mm×5mm, and the test sample was attached to a conductive tape, and after gold spraying, a Zeiss analytical scanning electron microscope was used to obtain a morphology photograph.
[0098] Modified melamine salt content test:
[0099] After the lithium-ion battery is discharged to 3.0V at a constant current of 0.1C, the lithium-ion battery is disassembled to obtain a positive electrode plate with a coating. The positive electrode plate is cleaned with N-methylpyrrolidone, and the modified melamine salt is separated from the positive electrode plate to obtain a suspension containing a coating. Take half, filter and dry at 85°C, and weigh the weight M1 of the modified melamine salt; the other half is not filtered and dried at 85°C, and the weight M2 of the coating composition is weighed. The mass percentage of melamine salt in the coating composition = M1 / M2×100%.
[0100] Particle size test:
[0101] After the lithium-ion battery is discharged to 3.0V at a constant current of 0.1C, the lithium-ion battery is disassembled to obtain a positive electrode plate with a coating. The positive electrode plate is cleaned with N-methylpyrrolidone, and the modified melamine salt is separated from the positive electrode plate, filtered and dried at 85°C to obtain a modified melamine salt powder. The modified melamine salt powder is dispersed in deionized water or alcohol, sodium hexametaphosphate dispersant is added, and ultrasonic stirring is performed for 10 minutes. The modified melamine salt is tested using a Malvern particle size tester (model MasterSizer 2000) to obtain the particle size Dv50 of the modified melamine salt.
[0102] Solubility test:
[0103] Preparation of the test electrolyte: Ethylene carbonate, propylene carbonate (PC) and diethyl carbonate (DEC) were mixed in a mass ratio of 1:3:6 as a base solvent, lithium salt LiPF6, ethyl acetate and fluoroethylene carbonate were mixed and added to the base solvent, and stirred evenly to obtain a test electrolyte. Based on the mass of the test electrolyte, the mass percentage of lithium salt LiPF6 is 15%, the mass percentage of ethyl acetate is 5%, the mass percentage of fluoroethylene carbonate is 5%, and the balance is the base solvent.
[0104] After the lithium-ion battery is discharged at a constant current of 0.1C to 3.0V, the lithium-ion battery is disassembled to obtain a positive electrode plate with a coating. The positive electrode plate is cleaned with N-methylpyrrolidone, and the modified melamine salt is separated from the positive electrode plate, filtered and dried at 85°C to obtain the modified melamine salt.
[0105] Take a modified melamine salt weighing 0.5 g, place it in 5 g of test electrolyte, store it at 85°C for 1 hour, filter the modified melamine salt, and dry it to obtain a modified melamine salt weighing W. The solubility calculation formula is s1 (g / g) = (0.5-W) / W / 5.
[0106] High temperature storage performance test:
[0107] In an environment of about 25°C, the lithium-ion battery is charged at a constant current of 0.5C to a voltage of about 4.5V, and charged at a constant voltage of 4.5V to a current lower than 0.05C, so that the lithium-ion battery is in a fully charged state of 4.25V. The thickness of the lithium-ion battery is tested. The fully charged lithium-ion battery is then placed in an oven at about 85°C for about 24 hours, and its thickness after storage is tested. The high-temperature storage expansion rate of the lithium-ion battery is calculated by the following formula:
[0108] High temperature storage expansion rate (%) = ((thickness after storage - thickness before storage) / thickness before storage) × 100%.
[0109] Impact test pass rate test:
[0110] The lithium-ion battery was placed at 25°C for 15 minutes to allow the lithium-ion battery to reach a constant temperature state, and then charged at a constant current of 1C to a voltage of 4.5V, and at a constant voltage of 4.5V to a current of 0.05C.
[0111] Under the test environment of 25℃, place the lithium-ion battery on the test table with the side with the battery cell code information facing up, and place a round bar with a diameter of 15.8mm at the center of the wide side of the lithium-ion battery. The round bar is perpendicular to the long axis of the lithium-ion battery. Use a 9.1±0.1kg weight to drop it vertically from a height of 610±25mm and drop it at the intersection of the round bar and the lithium-ion battery. The passing criteria: no fire, no explosion.
[0112] 20 lithium-ion batteries were tested in each embodiment and comparative example, and the impact test pass rate (%) = number of passed batteries / 20×100%.
[0113] Extrusion test:
[0114] The lithium-ion battery was placed at 25°C for 15 minutes to allow the lithium-ion battery to reach a constant temperature state, and then charged at a constant current of 1C to a voltage of 4.5V and a constant voltage of 4.5V to a current of 0.05C.
[0115] In a 25°C test environment, place the lithium-ion battery on the test table, use a blunt nail with a diameter of 6mm and a pressurization rate of 300N / min, start the test from the head step of the lithium-ion battery, 10±1mm away from the upper edge of the body, until the lithium-ion battery explodes and catches fire, and record the extrusion pressure (N) at this time.
[0116] Example 1-1
[0117] <Preparation of coating composition>
[0118] (1) Preparation of modified melamine polyphosphate: Add 2000ml of deionized water to a 5L reaction vessel, heat to 85°C, add 200g of melamine (C3N6H6) while stirring at 300rpm, and after it is highly dispersed, continue stirring for 30min to obtain a highly dispersed melamine precursor solution. Add 98g of pre-ground phosphoric acid powder and 4g of propylene glycol, control the temperature at 85°C, stir rapidly at 500rpm for 15min, then add 100g of phosphoric acid powder, and react at 95°C for 30min. After the reactants are cooled to room temperature, filter, wash the filter cake twice with an equal weight of 79°C deionized water, spray granulate and dry to obtain a white powder solid modified melamine polyphosphate.
[0119] (2) Preparation of coating composition 1: In a 20 L dispersion tank, 3 kg of the modified melamine polyphosphate and 0.3 kg of polyvinylidene fluoride binder were added in a mass ratio of 10:1, totaling 3.3 kg. 11.7 kg of N-methylpyrrolidone (NMP) solvent was added and dispersed and mixed uniformly to obtain coating composition 1.
[0120] (3) Preparation of coating composition 2: In a 20L dispersion tank, add 3kg of the above-mentioned modified melamine polyphosphate and 0.3kg of polyacrylic acid binder in a mass ratio of 10:1, totaling 3.3kg, and add 11.7kg of deionized water. Disperse and mix evenly to obtain coating composition 2.
[0121] <Preparation of positive electrode sheet>
[0122] The positive electrode active material lithium cobalt oxide, the conductive agent conductive carbon black (Super P), and the binder polyvinylidene fluoride (PVDF, weight average molecular weight Mw = 530000) are added to N-methylpyrrolidone (NMP) in a mass ratio of 96:2.5:1.5, and stirred evenly to form a positive electrode slurry with a solid content of 70wt%. The positive electrode slurry is evenly coated on one side of the positive electrode collector aluminum foil, dried at 85°C, and then the above steps are repeated on the other side of the aluminum foil to obtain a semi-finished positive electrode sheet coated with a positive electrode material layer on both sides, and then cold pressed and cut to obtain a semi-finished positive electrode sheet with a specification of 74mm×867mm. The coating composition 1 is applied to the surface of the positive electrode material layer on one side of the semi-finished positive electrode sheet away from the positive electrode collector by gravure roller transfer coating, and then the above steps are repeated on the surface of the positive electrode material layer on the other side of the semi-finished positive electrode sheet away from the positive electrode collector, and then dried in an oven at 85°C to obtain a positive electrode sheet. The coating weight of the coating composition on both sides of the positive electrode sheet is 6 mg / 5000 mm 2 .
[0123] <Preparation of Separator>
[0124] The substrate is a polyethylene polymer microporous membrane with a thickness of 5 μm and a porosity of 55% (from Enjie New Materials Technology Co., Ltd.). The coating composition 2 is applied to the surface of the substrate facing the positive electrode plate by gravure roller transfer coating, and dried in an oven at 55°C to obtain a separator. The coating weight of the coating composition on the substrate is 10 mg / 5000 mm 2 .
[0125] <Preparation of negative electrode sheet>
[0126] The negative electrode active material artificial graphite, thickener sodium carboxymethyl cellulose (CMC) and binder styrene butadiene rubber (SBR) were added to deionized water at a mass ratio of 96:2:2, and stirred evenly to form a negative electrode slurry with a solid content of 50wt%. The negative electrode slurry was evenly coated on one side of the negative electrode current collector copper foil, dried, and then the above steps were repeated on the other side of the copper foil to obtain a negative electrode sheet coated with a negative electrode active layer on both sides. After cold pressing and cutting, a negative electrode sheet with a specification of 74mm×867mm was obtained.
[0127] <Preparation of Electrolyte>
[0128] In an argon atmosphere glove box with a water content of less than 10 ppm, ethylene carbonate, ethyl acetate and fluoroethylene carbonate (FEC) were uniformly mixed at a mass ratio of 55:30:15 to obtain a basic solvent, and lithium salt LiPF6 was added and stirred to obtain an electrolyte. Among them, based on the total mass of the electrolyte, the mass percentage of lithium salt LiPF6 was 12.5%, and the remainder was the basic solvent.
[0129] <Preparation of lithium-ion batteries>
[0130] The prepared diaphragm, positive electrode sheet, diaphragm, and negative electrode sheet are stacked in order so that the diaphragm is between the positive electrode sheet and the negative electrode sheet to obtain a stacked electrode assembly. After welding the positive electrode ear and the negative electrode ear, the electrode assembly is placed in an aluminum-plastic film packaging bag, heat-sealed on all sides, leaving a liquid injection port, and the above-mentioned electrolyte is injected. After vacuum packaging, standing, formation, degassing and other processes, a lithium-ion battery is obtained.
[0131] Example 1-2
[0132] <Preparation of coating composition>
[0133] (1) Preparation of modified melamine cyanurate: Add 2000ml of deionized water to a 5L reaction vessel, heat to 85°C, add 200g of melamine (C3N6H6) while stirring at 300rpm, and after it is highly dispersed, continue stirring for 30min to obtain a highly dispersed melamine precursor solution. Add 163g of pre-ground cyanuric acid powder and 4g of propylene glycol, control the temperature at 85°C, stir rapidly at 500rpm for 15min, then add 163g of cyanuric acid powder, and react at 95°C for 30min. After the reactants are cooled to room temperature, filter, wash the filter cake twice with an equal weight of 79°C deionized water, spray granulate and dry to obtain modified melamine cyanurate as a white powder solid.
[0134] In (2) and (3), the modified melamine polyphosphate was replaced by modified melamine cyanurate, and the rest was the same as Example 1-1.
[0135] <Preparation of positive electrode sheet>, <Preparation of negative electrode sheet>, <Preparation of separator>, <Preparation of electrolyte> and <Preparation of lithium ion battery> are the same as those in Example 1-1.
[0136] Example 1-3 to Example 1-9
[0137] Except for adjusting Δt according to Table 1, the rest is the same as Example 1-2. The adjustment of Δt is achieved by adjusting the amount of the molecular modifier added during the preparation of the coating composition.
[0138] Example 1-10 to Example 1-13
[0139] Except for adjusting s1 according to Table 1, the rest is the same as Example 1-2. The adjustment of s1 is achieved by regulating the reaction temperature of melamine and the molecular modifier during the preparation of the coating composition.
[0140] Example 1-14 to Example 1-20
[0141] Except for adjusting the particle size Dv50 of the modified melamine salt according to Table 1, the rest is the same as Example 1-1.
[0142] Embodiment 1-21
[0143] Except for preparing coating composition 1 according to the following steps, the rest is the same as Example 1-1.
[0144] <Preparation of coating composition>
[0145] Preparation of coating composition 1: In a 20L dispersion tank, add 1.485kg of the modified melamine polyphosphate, 0.16kg of polyvinylidene fluoride binder and 1.685kg of LATP (Li 1.4 Al 0.4 Ti 1.6 (PO4)3) powder, with a mass ratio of 45:5:50, totaling 3.33 kg, was added with 11.7 kg of N-methylpyrrolidone solvent, and dispersed and mixed evenly to obtain a coating composition 1.
[0146] Example 1-22 to Example 1-24
[0147] Except for adjusting the mass percentage a of the modified melamine salt according to Table 1, the rest is the same as Example 1-19.
[0148] Among them, as the mass percentage of modified melamine salt a changes, the mass percentage of the binder remains unchanged, LATP (Li 1.4 Al 0.4 Ti 1.6The mass percentage of (PO4)3) changes accordingly, and the sum of the mass percentages of modified melamine salt, LATP and binder is 100%.
[0149] Example 1-25 to Example 1-28
[0150] Except for adjusting the mass percentage a of the modified melamine salt according to Table 1, the rest is the same as Example 1-1.
[0151] Among them, when the mass percentage a of the modified melamine salt changes, the mass percentage of the binder changes accordingly, and the sum of the mass percentages of the modified melamine salt and the binder is 100%.
[0152] Examples 1-29
[0153] Except for preparing the positive electrode sheet and the separator according to the following steps, the rest is the same as Example 1-1.
[0154] <Preparation of positive electrode sheet>
[0155] The positive electrode active material lithium cobalt oxide, the conductive agent conductive carbon black (Super P), and the binder polyvinylidene fluoride (PVDF, weight average molecular weight Mw = 530000) are added to N-methylpyrrolidone (NMP) in a mass ratio of 96:2.5:1.5, and stirred evenly to form a positive electrode slurry with a solid content of 70wt%. The positive electrode slurry is evenly coated on one side of the positive electrode current collector aluminum foil, dried at 85°C, and then the above steps are repeated on the other side of the aluminum foil to obtain a semi-finished positive electrode sheet coated with a positive electrode material layer on both sides. After cold pressing and cutting, a semi-finished positive electrode sheet with a specification of 74mm×867mm is obtained. The coating composition 1 is applied to the surface of the positive electrode material layer on one side of the semi-finished positive electrode sheet away from the positive electrode current collector by gravure roller transfer coating, and dried in an oven at 85°C to obtain a positive electrode sheet. The coating weight of the coating composition on one side of the positive electrode sheet is 6mg / 5000mm 2 .
[0156] <Preparation of Separator>
[0157] The substrate was a polyethylene polymer microporous membrane with a thickness of 5 μm and a porosity of 55% (from Enjie New Materials Technology Co., Ltd.).
[0158] Examples 1-30
[0159] Except for preparing the positive electrode sheet according to the following steps, the rest is the same as Example 1-1.
[0160] <Preparation of positive electrode sheet>
[0161] The positive electrode active material lithium cobalt oxide, the conductive agent conductive carbon black (Super P), and the binder polyvinylidene fluoride (PVDF, weight average molecular weight Mw=530000) are added to N-methylpyrrolidone (NMP) at a mass ratio of 96:2.5:1.5, and stirred evenly to form a positive electrode slurry with a solid content of 70wt%. The positive electrode slurry is evenly coated on one side of the positive electrode collector aluminum foil, dried at 85°C, and then the above steps are repeated on the other side of the aluminum foil to obtain a semi-finished positive electrode sheet coated with a positive electrode material layer on both sides, and then cold pressed and cut to obtain a positive electrode sheet with a specification of 74mm×867mm.
[0162] Example 2-1 to Example 2-3
[0163] Except for adjusting the type of molecular modifier according to Table 2, the rest is the same as Example 1-1.
[0164] Embodiment 2-4
[0165] Except for adjusting the type of adhesive according to Table 2, the rest is the same as Example 1-1.
[0166] Example 2-5 to Example 2-10
[0167] Except for adjusting the mass percentage b of the molecular modifier according to Table 2, the rest is the same as Example 1-1.
[0168] When the mass percentage b of the molecular modifier changes, the mass percentage of the inorganic acid or organic acid and the mass percentage of melamine change accordingly, and the molar ratio of the functional groups of the inorganic acid or organic acid and melamine remains unchanged at 101:79. The sum of the mass percentages of the inorganic acid or organic acid, melamine and the molecular modifier is 100%.
[0169] Example 2-11 to Example 2-16
[0170] The same as Example 1-1 except that the absolute value m of the pH difference between the modified melamine salt and the binder is adjusted according to Table 2. The absolute value m of the pH difference can be changed by mixing the same modified melamine salt with different types of binders.
[0171] Comparative Example 1
[0172] Except for preparing the positive electrode sheet and the separator according to the following steps, the rest is the same as Example 1-1.
[0173] <Preparation of positive electrode sheet>
[0174] The positive electrode active material lithium cobalt oxide, the conductive agent conductive carbon black (Super P), and the binder polyvinylidene fluoride (PVDF, weight average molecular weight Mw=530000) are added to N-methylpyrrolidone (NMP) at a mass ratio of 96:2.5:1.5, and stirred evenly to form a positive electrode slurry with a solid content of 70wt%. The positive electrode slurry is evenly coated on one side of the positive electrode collector aluminum foil, dried at 85°C, and then the above steps are repeated on the other side of the aluminum foil to obtain a semi-finished positive electrode sheet coated with a positive electrode material layer on both sides, which is then cold pressed and cut to obtain a positive electrode sheet with a specification of 74mm×867mm.
[0175] <Preparation of Separator>
[0176] The substrate was a polyethylene polymer microporous membrane with a thickness of 5 μm and a porosity of 55% (from Enjie New Materials Technology Co., Ltd.).
[0177] Comparative Example 2
[0178] Except for preparing the positive electrode sheet according to the following steps, the rest is the same as Example 1-2.
[0179] <Preparation of positive electrode sheet>
[0180] Add 2000ml of deionized water to a 5L reaction vessel, heat to 85°C, add 200g of melamine (C3N6H6) while stirring at 300rpm, and after it is highly dispersed, continue stirring for 30min to obtain a highly dispersed melamine precursor solution. Add 98g of pre-ground cyanuric acid powder, control the temperature at 85°C, stir rapidly at 500rpm for 15min, then add 100g of cyanuric acid powder, and react at 95°C for 30min. After the reactants are cooled to room temperature, filter them, wash the filter cake twice with an equal weight of 79°C deionized water, spray granulate and dry to obtain melamine cyanurate as a white powder solid.
[0181] The positive electrode active material lithium cobalt oxide, the conductive agent conductive carbon black (Super P), and the binder polyvinylidene fluoride (PVDF, weight average molecular weight Mw=530000) are added to N-methylpyrrolidone (NMP) at a mass ratio of 96:2.5:1.5, and stirred evenly to form a positive electrode slurry with a solid content of 70wt%. The positive electrode slurry is evenly coated on one side of the positive electrode collector aluminum foil, dried at 85°C, and then the above steps are repeated on the other side of the aluminum foil to obtain a semi-finished positive electrode sheet coated with a positive electrode material layer on both sides, and then cold pressed and cut to obtain a semi-finished positive electrode sheet with a specification of 74mm×867mm.
[0182] In a 20L dispersion tank, add 3kg of modified melamine cyanurate and 0.3kg of polyvinylidene fluoride binder, with a mass ratio of 10:1, a total of 3.3kg, and add 11.7kg of N-methylpyrrolidone (NMP), disperse and mix evenly to obtain a coating slurry. The slurry is coated on the surface of the positive electrode material layer on both sides of the semi-finished positive electrode sheet away from the positive electrode current collector by gravure roller transfer coating, and dried in an oven. The coating weight of the coating composition on both sides of the positive electrode sheet is 6mg / 5000mm 2 .
[0183] Comparative Example 3
[0184] The same as Example 1-2 except that the type of modified melamine salt and the endothermic temperature difference Δt are adjusted according to Table 1. The adjustment of Δt is achieved by regulating the amount of the molecular modifier added during the preparation of the coating composition.
[0185] The preparation parameters and performance parameters of each embodiment and comparative example are shown in Table 1 and Table 2.
[0186] Table 1
[0187] Note: “ / ” in Table 1 indicates that the corresponding preparation parameters or substances do not exist; “a” in Examples 1-1 to 1-29 and Comparative Example 3 in Table 1 is the mass percentage of the modified melamine salt in coating composition 1; “a” in Examples 1-30 is the mass percentage of the modified melamine salt in coating composition 2.
[0188] It can be seen from Examples 1-1 to 1-30 and Comparative Examples 1 to 3 that the lithium ion battery of the embodiment of the present application contains a modified melamine salt, and the endothermic temperature difference Δt between the modified melamine salt and the unmodified melamine salt is regulated within the range of 5°C≤Δt≤100°C, which enables the lithium ion battery to have a lower high-temperature storage expansion rate, and at the same time has a higher impact test pass rate and extrusion pressure, indicating that the lithium ion battery of the embodiment of the present application has good high-temperature storage performance and mechanical safety performance. While the secondary battery of the comparative example does not contain a modified melamine salt or the endothermic temperature difference Δt between the modified melamine salt and the unmodified melamine salt is not within the range of 5°C≤Δt≤100°C, the lithium ion battery of the comparative example has a higher high-temperature storage expansion rate, and at the same time has a lower impact test pass rate and extrusion pressure, indicating that the lithium ion battery of the comparative example has poor high-temperature storage performance and safety performance.
[0189] The endothermic temperature difference Δt between the modified melamine salt and the unmodified melamine salt usually affects the high temperature storage performance and mechanical safety performance of the lithium ion battery. It can be seen from Examples 1-2 to 1-9, Comparative Example 2 and Comparative Example 3 that when the endothermic temperature difference Δt between the modified melamine salt and the unmodified melamine salt is regulated within the scope of the present application, the lithium ion battery can have a lower high temperature storage expansion rate, and at the same time have a higher impact test pass rate and extrusion pressure, indicating that the lithium ion battery provided in the present application has good high temperature storage performance and mechanical safety performance.
[0190] The solubility s1 of the modified melamine salt in the test electrolyte usually affects the high temperature storage performance and mechanical safety performance of the lithium-ion battery. It can be seen from Examples 1-2, 1-10 to 1-13 that when the solubility s1 of the modified melamine salt in the test electrolyte is regulated within the scope of this application, the lithium-ion battery can have a lower high temperature storage expansion rate, and at the same time have a higher impact test pass rate and extrusion pressure, indicating that the lithium-ion battery provided in this application has good high temperature storage performance and mechanical safety performance.
[0191] The thermal weight loss mass residual rate w of the modified melamine salt usually affects the high temperature storage performance and mechanical safety performance of the lithium-ion battery. It can be seen from Examples 1-1 to 1-9 that when the thermal weight loss mass residual rate w characterized by the modified melamine salt on the TG curve is regulated within the scope of this application, the lithium-ion battery can have a lower high temperature storage expansion rate, and at the same time have a higher impact test pass rate and extrusion pressure, indicating that the lithium-ion battery provided by this application has good high temperature storage performance and mechanical safety performance.
[0192] The particle size Dv50 of the modified melamine salt usually affects the high temperature storage performance and mechanical safety performance of the lithium ion battery. It can be seen from Examples 1-1, 1-14 to 1-20 that when the particle size Dv50 of the modified melamine salt is adjusted within the scope of the present application, the lithium ion battery can have a lower high temperature storage expansion rate, and at the same time have a higher impact test pass rate and extrusion pressure, indicating that the lithium ion battery provided by the present application has good high temperature storage performance and mechanical safety performance.
[0193] Based on the mass of the coating composition, the mass percentage a of the modified melamine salt usually affects the high temperature storage performance and mechanical safety performance of the lithium ion battery. It can be seen from Examples 1-1, 1-21 to 1-28 that when the mass percentage a of the modified melamine salt is adjusted within the scope of the present application, the lithium ion battery can have a lower high temperature storage expansion rate, and at the same time have a higher impact test pass rate and extrusion pressure, indicating that the lithium ion battery provided by the present application has good high temperature storage performance and mechanical safety performance.
[0194] The location of the coating composition usually affects the high temperature storage performance and mechanical safety performance of the lithium-ion battery. It can be seen from Examples 1-1, 1-29 and 1-30 that when the location of the coating composition is adjusted within the scope of the present application, the lithium-ion battery can have a lower high temperature storage expansion rate, and at the same time have a higher impact test pass rate and extrusion pressure, indicating that the lithium-ion battery provided by the present application has good high temperature storage performance and mechanical safety performance.
[0195] Figure 1 This is the DSC curve of the modified melamine cyanurate of Example 1-2 of the present application. It can be seen that the peak temperature of the modified melamine cyanurate of Example 1-2 is 403°C; Figure 2 From the DSC curve of the unmodified melamine cyanurate in Comparative Example 2 of the present application, it can be seen that the peak temperature of the unmodified melamine cyanuric acid is 443°C; therefore, by comparing the peak temperatures of the two, it can be obtained that the difference Δt between the endothermic temperatures of the two is 40°C. Figure 3 This is the TG curve of the modified melamine cyanurate of Example 1-2 of the present application. It can be seen that the thermal weight loss mass residual rate of the modified melamine cyanurate is 14.97%. Figure 4 This is the TG curve of the unmodified melamine cyanurate in Comparative Example 2 of the present application. It can be seen that the thermal weight loss mass residual rate of the unmodified melamine cyanurate is 0%. Figure 5 This is a scanning electron microscope photograph of the unmodified melamine cyanurate of Comparative Example 2 of the present application. Figure 5 It can be seen that no carbonized region exists in the unmodified melamine polyphosphate. Figure 6 This is a scanning electron microscope photo of the modified melamine cyanurate of Example 1-2 of the present application, from Figure 6 It can be seen that the modified melamine urate has a carbonized area, and the carbonized product can maintain the coating structure and reduce the possibility of further contact and short circuit between the positive electrode and the negative electrode; Figure 7 This is a scanning electron microscope photo of the modified melamine cyanurate of Examples 1-4 of the present application, from Figure 7 It can be seen that the modified melamine urate has a carbonized area, compared with Figure 6 The particle size of the carbonized product is small, indicating that the thermal weight loss mass residual rate is small.
[0196] Table 2
[0197] When a modified melamine salt is prepared by introducing a molecular modifier during the reaction of melamine with an inorganic acid or an organic acid, the type of the molecular modifier usually affects the high temperature storage performance and mechanical safety performance of the lithium ion battery. It can be seen from Examples 1-1, 2-1 and 2-3 that when the type of the molecular modifier is adjusted within the scope of this application, the lithium ion battery can have a lower high temperature storage expansion rate, and at the same time have a higher impact test pass rate and extrusion pressure, indicating that the lithium ion battery provided by this application has good high temperature storage performance and mechanical safety performance.
[0198] The coating composition includes a modified melamine salt and a binder, and the type of the binder usually affects the high temperature storage performance and mechanical safety performance of the lithium-ion battery. It can be seen from Examples 1-1 and 2-4 that when the type of binder in the coating composition is adjusted within the scope of this application, the lithium-ion battery can have a lower high temperature storage expansion rate, and at the same time have a higher impact test pass rate and extrusion pressure, indicating that the lithium-ion battery provided by this application has good high temperature storage performance and mechanical safety performance.
[0199] Based on the total mass of the modified melamine salt, the mass percentage b of the molecular modifier usually affects the high temperature storage performance and mechanical safety performance of the lithium ion battery. It can be seen from Examples 1-1, 2-5 to 2-10 that by regulating the mass percentage b of the molecular modifier within the scope of this application, the lithium ion battery can have a lower high temperature storage expansion rate and a higher impact test pass rate and extrusion pressure, indicating that the lithium ion battery of the embodiment of this application has good high temperature storage performance and mechanical safety performance.
[0200] The absolute value m of the pH difference between the modified melamine salt and the binder usually affects the high temperature storage performance and mechanical safety performance of the lithium ion battery. It can be seen from Examples 2-1, 2-11 to 2-16 that by adjusting the absolute value m of the pH difference between the modified melamine salt and the binder within the scope of this application, the lithium ion battery can have a lower high temperature storage expansion rate, and at the same time have a higher impact test pass rate and extrusion pressure, indicating that the lithium ion battery of the embodiment of this application has good high temperature storage performance and mechanical safety performance.
[0201] It should be noted that, in this article, the terms "comprises", "includes" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, article or apparatus that includes a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or apparatus.
[0202] Each embodiment in this specification is described in a related manner, and the same or similar parts between the embodiments can be referenced to each other, and each embodiment focuses on the differences from other embodiments.
[0203] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present application shall be included in the scope of protection of the present application.
Claims
1. A coating composition comprising a modified melamine salt and a binder, wherein: The endothermic temperature of the modified melamine salt characterized on the differential scanning calorimetry curve is lower than the endothermic temperature of the unmodified melamine salt, and the difference is Δt°C, 5≤Δt≤100.
2. The coating composition according to claim 1, wherein 15≤Δt≤60.
3. The coating composition according to claim 1, wherein The solubility of the modified melamine salt in the test electrolyte is s1g / g, s1<0.
1.
4. The coating composition according to claim 3, wherein s1≤0.02。 5. The coating composition according to claim 1, wherein The thermal weight loss mass residual rate of the modified melamine salt characterized by the thermogravimetric curve is w%, and 1≤w≤35.
6. The coating composition according to claim 5, wherein 4.56≤w≤33。 7. The coating composition according to claim 1, wherein The particle size of the modified melamine salt is Dv50 μm, satisfying 0.1≤Dv50≤3.
0.
8. The coating composition according to claim 7, wherein 0.3≤Dv50≤1.
5.
9. The coating composition according to claim 1, wherein Based on the mass of the coating composition, the mass percentage of the modified melamine salt is a %, satisfying 50≤a≤99.
10. The coating composition according to claim 9, wherein 70≤a≤95。 11. The coating composition according to claim 1, wherein The binder includes at least one of polyacrylic acid, polyacrylate, polyvinylidene fluoride, styrene-butadiene rubber, sodium carboxymethyl cellulose, polyvinyl alcohol, polyimide or aluminum hydroxide sol.
12. The coating composition according to claim 1, wherein The modified melamine salt is obtained by introducing a molecular modifier during the reaction of melamine with an inorganic acid or an organic acid, wherein the molecular modifier contains a plurality of hydroxyl groups or a plurality of amino groups.
13. The coating composition according to claim 12, wherein The molecular modifier includes a high molecular weight polymer of polyhydroxyl polymerized from a small molecular weight compound, and the high molecular weight polymer of polyhydroxyl polymer includes at least one of polyvinyl alcohol, polyethylene glycol or polymeric polyol.
14. The coating composition according to claim 12, wherein The molecular modifier includes a polyhydroxy compound or a polyamino compound; the polyhydroxy compound includes at least one of ethylene glycol, propylene glycol, glycerol, butylene glycol, hexylene glycol, pentaerythritol, ethylenediaminetetraacetic acid, trimethylolethane, xylitol or sorbitol; the polyamino compound includes at least one of ethylenediamine or hexamethylenetetramine.
15. The coating composition according to claim 12, wherein The inorganic acid includes at least one of phosphoric acid, pyrophosphoric acid or boric acid; the organic acid includes at least one of cyanuric acid, phthalic acid, oxalic acid, phytic acid or 2-carboxyethylphenylphosphinic acid.
16. The coating composition according to claim 12, wherein: Based on the total mass of the modified melamine salt, the mass percentage of the molecular modifier is b %, satisfying 0.1≤b≤15.
0.
17. The coating composition according to claim 16, wherein 0.5≤b≤5.0。 18. The coating composition according to claim 1, wherein The absolute value of the pH difference between the modified melamine salt and the binder is m, which satisfies 0≤m≤5.
0.
19. The coating composition according to claim 18, wherein 0≤m≤2.5。 20. An electrochemical device, wherein: The electrochemical device comprises the coating composition of any one of claims 1 to 19.
21. The electrochemical device according to claim 20, comprising a positive electrode sheet and a separator, wherein: The coating composition is disposed on the surface of the separator facing the positive electrode sheet and / or on at least one surface of the positive electrode sheet.
22. An electronic device, wherein: The electronic device comprises the electrochemical device according to claim 20 or 21.
Citation Information
Patent Citations
Rodlike crystalline melamine cyanurate fire retardant and preparation method thereof
CN102174213A
Lithium ion battery composite pole piece, preparation method thereof and lithium ion battery
CN105118970A
Environmentally friendly low-smoke halogen-free sheath material with high fire retardant performance
CN108822469A
Ceramic slurry for high-temperature-resistant lithium ion battery diaphragm and application of ceramic slurry
CN110627411A
Flame-retardant polyester yarn and preparation method thereof
CN113502559A